AlGaAs/GaAs superlattice photocathode grown by molecular beam epitaxy: correspondence between room temperature photoluminescence and quantum efficiency. (15th January 2021) - Morita, Iori; Ishikawa, Fumitaro; Honda, Anna; Sato, Daiki; Koizumi, Atsushi; Nishitani, Tomohiro; Tabuchi, Masao
Abstract: The semiconductor photocathode with AlGaAs/GaAs superlattice structures, which is a highly durable electron beam source with low energy dispersion, were grown by molecular beam epitaxy. The sample showed a step-like quantum efficiency spectrum of photoelectron emission, indicating its applicability to photocathodes. The optimization of room temperature photoluminescence provides the improvement of the photocathode quantum efficiency up to 0.5%, promising for its further improvement and realistic applications.